Implementasi Kebijakan Pengembangan Kabupaten/Kota Layak Anak Di Provinsi Kalimantan Tengah - Muhammad Riban Satia; Triwik Puji Rahayu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The purpose of this research is to determine the implementation of the district/city Worthy Development policy (KLA) in central Kalimantan province. The method used is qualitative descriptive. Data collection techniques using interviews, observations and documentation. The data analysis used is the interactive model of Miles & Huberman with data reduction, data presentation, and conclusion withdrawal. The results of this research show that the policy of district development/city worthy of children (KLA) has been implemented in central Kalimantan province, although not optimal because of the lack of effective communication done to the public. Another thing that hinders the policy of district/city development worthy of children is because of the limited budget resources so that the implementation of the policy of District/city development worthy of children in central Kalimantan province becomes hampered. The advice that can be conveyed is to the Women Empowerment Department, Child protection, population control and family planning (P3A-PPKB) with the Office of Population Control and family planning, women empowerment, protection District level children to conduct more active and sustainable communication to the public through the installation of banners, banners, and creative posters or through other advertising media to improve the Community's understanding and awareness So that the active role of the community in the process of implementing district/city worthy development policy can increase. Approach the private sector to allocate the budget of their Corporate Social Responsibility to support the implementation of the district/city proper development policy in Central Kalimantan province.